Integrating technology for meaningful learning - Grabe, Mark (Houghton Mifflin Co., 2007)
Integrating Technology for Meaningful Learning, 5/e, provides a unique, inviting approach to introducing the use of technology in the K-12 classroom. Offering an abundance of authentic, hands-on projects, the text provides future classroom teachers with the essential information and motivation to use technology as an everyday tool. The authors strike an important balance between practical applications and theoretical issues so that teachers can concentrate on the connections between learning tasks and the mental activities of students. This new edition offers expanded coverage of the Internet as a tool for communication and inquiry and includes updated coverage of all emergent technologies.